Fishing debris in the Australian marine environment - Jones, Madeleine M. (Commonwealth of Australia ParkesAu, 1994)
Looks at the effects of fishing debris on the Australian marine environment and marine animals. Highlights action taken both in Australia and overseas to reduce debris through education programmes, development of plastic free gear, port disposal facilities and clean-up programmes.